TSV-integrated surface electrode ion trap for scalable quantum information processing - Zhao, Peng (2021)
In this study, we report the first Cu-filled through silicon via (TSV) integrated ion trap. TSVs are placed directly underneath electrodes as vertical interconnections between ion trap and a glass interposer, facilitating the arbitrary geometry design with increasing electrodes numbers and evolving complexity. The integration of TSVs reduces the form factor of ion trap by more than 80%, minimizing parasitic capacitance from 32 to 3 pF. A low RF dissipation is achieved in spite of the absence of ground screening layer. The entire fabrication process is on 12-inch wafer and compatible with established CMOS back end process. We demonstrate the basic functionality of the trap by loading and laser-cooling single 88Sr+ ions. It is found that both heating rate (17 quanta/ms for an axial frequency of 300 kHz) and lifetime (~30 minutes) are comparable with traps of similar dimensions. This work pioneers the development of TSV-integrated ion traps, enriching the toolbox for scalable quantum computing.